Seismic strength of adobe masonry - Vargas Neumann, Julio; Bariola Bernales, Juan; Blondet, Marcial; Mehta, Povindar K. (Pontificia Universidad Católica del Perú. Departamento de Ingeniería, 1984)
This paper presents the main conclusions and recommendations of the Research Project "Earthen Buildings in Seismic Areas", developed in the Catholic University of Peru (PUC) in 1983. The most important soil characteristics from the viewpoint of the strength of adobe masonry are first studied. Subsequently, based on the acquired knowledge, the effect of some natural additives to the soil is investigated. Simple field tests, devised to identify the most adequate materials for adobe construction and to be easily transmitted to the potential adobe builder are finally proposed.
Keywords: Adobe; Adictivos; https://purl.org/pe-repo/ocde/ford#2.01.01